DAMA : weaving lives - Sriram, EmD. Es., 1962- (SAGE Knowledge. Cases., 2017)
The previous year had not been particularly good for DAMA. Its largest buyer of pre-ordered fabric, Fabindia was going through some restructuring of how they handled logistics and had not bought an inch of fabric from them a sharp fall from buying 50 percent of DAMAs output. However, DAMA continued to market its procurement from the weavers through its strategy of selling to bulk buyers, retail exhibitions and home selling and did not suffer a major setback in terms of a stockpile. But the vulnerability was evident and the changes in the larger market would affect the way the group functioned. It called for some introspection on what they stood for as a group. It was a complex structure and needed intervention at multiple levels in order to keep the entire cycle going. Prioritization of areas of intervention was an issue and DA was constantly grappling with the emerging complex situation.